Development of Muzakki Loyalty Model Considering Service Quality and Sharia Governance: A Literature Review - Susanto, Mei; Pujiyanto, Eko; Damayanti, Retno Wulan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to develop a Muzakki loyalty model through a systematic literature review (SLR) approach. Methodology: The SLR process was conducted using the PRISMA scheme to select relevant literature form the Scopus database. Out of 27 identified articles, 6 were selected for further analysis. Results: The findings show that service quality affects Muzakki satisfaction, while personal factors, such as sharia governance and transparency in zakat management influence trust and Muzakki loyalty. Islamic work ethics and trust, also play a significant role in increasing loyalty and the amount of zakat contributions. Applications/Originality/Value: This study highlights the importance of effective zakat management by considering the dimensions of Muzakki loyalty to enhance sustained participation in zakat payments. The findings contribute to the broader discourse on sustainable development and highlight the potential applicability of these principles to other sectors. By applying these insights, industries and organizations can adopt similar strategies to ensure longterm sustainability and stakeholder engagement.